Artificial Intelligence (AI) Adoption in Pesantren: Challenges and Readiness - Yazid, Ahmad Subhan (Proceeding International Conference on Religion, Science and Education, 2024)
The presence of Artificial Intelligence (AI) has impacted various sectors of life, including education, in which there are pesantren entities. This article aims to discuss how the readiness of pesantren in adopting AI in learning at the same time as the challenge of maintaining the values and traditions of pesantren as the driving force of Islamic religious education in Indonesia. This research was conducted using the literature method with data collection techniques in the form of literature reviews from scientific articles and various relevant sources of information. The data obtained is then analyzed and compiled to obtain coherent information and good conclusions. As a result, there are at least three attitudes of pesantren in dealing with the development of information technology: open, closed, and partially open. There are several opportunities for AI utilization to be applied by pesantren along with its challenges. As an unstoppable phenomenon, the development of AI needs to be adopted by pesantren, both actively and passively, while maintaining the values and culture of pesantren.